Front Cover: Crystal Growth and Characterization of the Mixed‐Cation Rb+/[XeF5]+ and Cs+/[XeF5]+ Salts (Eur. J. Inorg. Chem. 21/2017). Issue 21 (8th May 2017) - Mazej, Zoran; Goreshnik, Evgeny
Abstract : The cover picture shows one of the possibilities after reactions of APnF6 (A = [H3 O] +, K, Rb, Cs; Pn = P, As, Sb, Bi), ABF4 (A = K, Cs), and Cs2 MnF6 with [XeF5 ][PnF6 ] (Pn = As, Sb), that is, the formation of a new type of mixed‐cation [XeF5 ] + /Cs + and [XeF5 ] + /Rb + salts of [SbF6 ] – and [BiF6 ] – /[SbF6 ] – with formula Rb[XeF5 ][SbF6 ]2, Cs[XeF5 ][SbF6 ]2, and Cs[XeF5 ][Bi x Sb1– x F6 ]2 (x ≈ 0.37–0.39). The determination of their crystal structure showed that all three new compounds crystallize in two modifications at low (α‐phase, 150 K) and high (β‐phase, 296 K) temperature. The other two possibilities observed in this system are double displacement reactions or no reaction at all. Details are discussed in the article by Z. Mazej and E. Goreshnik on page 2800 ff (DOI:10.1002/ejic.201700097 ). For more on the story behind the cover research, see the Cover Profile (DOI:10.1002/ejic.201700425 ).